2005
DOI: 10.1016/j.jhsb.2004.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Tendon Rehabilitation a Prospective Trial Comparing Three Rehabilitation Regimes

Abstract: Forty-two patients with 46 complete extensor tendon injuries were prospectively allocated to one of three rehabilitation regimes: static splintage; interphalangeal joint mobilization with metacarpophalangeal joint immobilization or; the "Norwich" regime. All 42 patients were operated on by one surgeon and assessed by one hand therapist. At 4 weeks the total active motion in the static splintage group was significantly reduced but by 12 weeks there was no difference between the regimes. There was no difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 10 publications
3
45
0
Order By: Relevance
“…Bulstrode et al also compared static immobilization with interphalangeal joint and MCP joint active mobilization after repair of zone V and VI lacerations. 8 Similar to Mowlavi, they found that both active mobilization groups demonstrated increased TAM at 4 weeks (p Ͻ .01) but that no significant differences could be found at 3 months. 8 In a randomized, controlled study in 2000, Khandwala compared dynamic active mobilization with active mobilization in zone V and VI extensor tendon repairs.…”
Section: Rehabilitationsupporting
confidence: 52%
See 1 more Smart Citation
“…Bulstrode et al also compared static immobilization with interphalangeal joint and MCP joint active mobilization after repair of zone V and VI lacerations. 8 Similar to Mowlavi, they found that both active mobilization groups demonstrated increased TAM at 4 weeks (p Ͻ .01) but that no significant differences could be found at 3 months. 8 In a randomized, controlled study in 2000, Khandwala compared dynamic active mobilization with active mobilization in zone V and VI extensor tendon repairs.…”
Section: Rehabilitationsupporting
confidence: 52%
“…8 Similar to Mowlavi, they found that both active mobilization groups demonstrated increased TAM at 4 weeks (p Ͻ .01) but that no significant differences could be found at 3 months. 8 In a randomized, controlled study in 2000, Khandwala compared dynamic active mobilization with active mobilization in zone V and VI extensor tendon repairs. Each group had 50 patients, but no statistical differences in TAM could be found.…”
Section: Rehabilitationsupporting
confidence: 52%
“…[3][4][5] Static or dynamic splinting and early active or early passive mobilization have been investigated. [1][2][3][4][5][6][7][8][9][10][11][12][13] The evidence regarding the best mobilization strategy is insufficient. 2 In later stages of rehabilitation, protocols of progressive loading exercises against a gradually increasing resistance might be added.…”
mentioning
confidence: 99%
“…37 Early active mobilization within the constraints of a thermoplastic splint (Norwich regimen) in which the wrist was immobilized at 45 degrees of extension, the MP joints in at least 50 degrees of flexion and the interphalangeal joints in neutral, have also been shown to give good results in zones V and VI injuries with a TAM of 160 degrees after 4 weeks. 38 Zones I and II injuries (mallet finger injuries) are treated by full immobilization. 37 and it limits tendon gliding within fibrous synovial sheaths.…”
Section: Rehabilitationmentioning
confidence: 99%